Conocimiento de los derechos del paciente hospitalizado y su aplicación por parte del personal de enfermería del Hospital Regional Isidro Ayora - Muñoz Guayanay, Judith Maribel (2014)
This research work was developed through a type of descriptive and cross-sectional study, which allowed to determine the relationship between the knowledge and the application of the rights of the patient hospitalized from the nursing staff of the Hospital Regional “Isidro Ayora”. Internal medicine, obstetrics and surgery areas, participated in the study, 23 nurses and 90 hospitalized patients; the instrument used for the collection of the information were two questionnaires: one aimed at the measurement of the knowledge that the professional staff of nursing have on the rights of the patient and the other aimed at hospitalized patients to measure their application. The results were: that nurses to 57 % "agrees" that the user should receive a dignified and respectful treatment and the 52 %" agrees" that they have the right to informed consent. In terms of enforcement of rights by nurses 80% of patients considered that "almost always" are provided with adequate care; While a high percentage of 70% of the patients consider that professional nursing staff "sometimes" have acted ethically, in the same way they stated "sometimes" to respect the right to refuse care or treatment and 24% considers that 'never' nurses have explained to them that they have the right to expropriation when they do not receive proper medical care. It is important that the leaders of the different areas of hospitalization of Hospital Regional Isidro Ayora, should carried out workshops which concerned the rights of the patient, to reinforce the expertise of the personnel and these learning could be applied in order to improve the relation between nurse- patient. Keywords: Knowledge, application of the patient's rights.